2017
DOI: 10.1039/c7sc04083k
|View full text |Cite
|
Sign up to set email alerts
|

A thiocyanopalladation/carbocyclization transformation identified through enzymatic screening: stereocontrolled tandem C–SCN and C–C bond formation

Abstract: Thiocyanopalladation/carbocyclization chemistry: C–SCN bond installation, carbocyclization, and opportunities for structural diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 131 publications
1
14
0
Order By: Relevance
“…Recently, Berkowitz and co-workers reported a formal thiocyanopalladation/carbocyclization transformation of enynes 98 and its parametrization and optimization by using a new elevated-temperature platebased version of the visual colorimetric enzymatic screening method for reaction discovery (Scheme 29). 37 In this cyclization, the thiocyano group served as the nucleophile, and various O-, N-, C-, or S-bridged cycles 99 containing an allylic C-SCN bond were successfully obtained through catalysis by PdCl 2 (PhCN) 2 . Substrate screening showed that trans-thiocyanopalladation took place predominantly for the N-, C-, or O-tethered alkynes, in accord with observations on other reported nucleopalladation-initiated enyne cyclizations.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…Recently, Berkowitz and co-workers reported a formal thiocyanopalladation/carbocyclization transformation of enynes 98 and its parametrization and optimization by using a new elevated-temperature platebased version of the visual colorimetric enzymatic screening method for reaction discovery (Scheme 29). 37 In this cyclization, the thiocyano group served as the nucleophile, and various O-, N-, C-, or S-bridged cycles 99 containing an allylic C-SCN bond were successfully obtained through catalysis by PdCl 2 (PhCN) 2 . Substrate screening showed that trans-thiocyanopalladation took place predominantly for the N-, C-, or O-tethered alkynes, in accord with observations on other reported nucleopalladation-initiated enyne cyclizations.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…During the course of our studies, Chen and co-workers reported a very similar method which required not only an elevated temperatures (100 °C), but a large excess of oxidants and stoichiometric amounts of strong base Cs 2 CO 3 [ 33 ], while, we found that only a slightly excess of the oxidants and catalytic amount of pyridine already could promote the C-H thiocyanation of N -arylacrylamides at 75 °C, making such a protocol easy to handle and scalable. Notably, in contrast to other oxindole syntheses, the resulting products, substituted 2-oxindoles with an appended SCN group, can be used to create further molecular complexity and diversity around the privileged scaffold of 2-oxindoles or can be applied for bioorthogonal transformation under physiological conditions [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A colorimetric version of ISES has also been developed that utilizes a visible dye chromophore as redox cofactor for a peroxidase enzyme‐based readout (Friest, Broussy, Chung, & Berkowitz, ; Malik et al, ). This assay was deployed to increase throughput (1152 combinations) to identify new (pseudo)halometallation/carbocyclization transformations (Figure ; ).…”
Section: Introductionmentioning
confidence: 99%